Investissement, progrès technique et croissance économique - Davenport, Paul (L'Actualité économique, 1982)
AbstractThis paper combines a critical review of the current state of the theory of economic growth with some suggestions for new directions in growth theory. The development of the neoclassical theory of growth and distribution is surveyed, with emphasis on the distribution theory of J.B. Clark, the regression analysis of C.W. Cobb and P.H. Douglas, the growth accounting of R.M. Solow and E.F. Denison, and the reswitching controversy, involving critical contributions by Joan Robinson, Piero Sraffa, and Luigi Pasinetti. Neoclassical growth models, including vintage models, are based on the theoretical separation of investment and technical change, which leads to the curious conclusion that investment is not a central part of the growth process. Post-Keynesian growth models, such as those of Nicholas Kaldor and John Cornwall, deny that such a separation is theoretically or empirically meaningful, and instead put investment at the heart of the growth process. The paper constructs a growth model along post-Keynesian lines, in which the growth rate, the distribution of income, and the normal unemployment rate are endogenous functions of the propensity to invest.